2018
DOI: 10.3126/jpahs.v5i2.23982
|View full text |Cite
|
Sign up to set email alerts
|

Depression among patients undergoing maintenance hemodialysis at a tertiary care center in Kathmandu, Nepal

Abstract: Introductions:Patients with chronic kidney disease have a high burden of somatic symptoms which may be due to depression. This study analyses occurrence of depression in patients with chronic kidney disease (CKD) undergoing hemodialysis (HD) at a tertiary care center in Kathmandu, Nepal.  Methods: This is a retrospective study done at Patan Hospital, a tertiary care teaching hospital of Patan Academy of Health sciences, Lalitpur, Nepal. Translated in Nepali language and validated Beck Depression Inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…the research by Manandhar et al did not show significant differences between the level of depression and gender, place of residence, education, amount of alcohol consumed and the presence of comorbidities. however, a relationship between the level of depression and employment status was demonstrated [22].…”
Section: Key Resultsmentioning
confidence: 98%
“…the research by Manandhar et al did not show significant differences between the level of depression and gender, place of residence, education, amount of alcohol consumed and the presence of comorbidities. however, a relationship between the level of depression and employment status was demonstrated [22].…”
Section: Key Resultsmentioning
confidence: 98%
“…One study done in Nepal reported similar findings where the rate of depression was higher among those undergoing dialysis for less than one year. 10 One possible reason for this finding may be that being diagnosed with chronic illness leading to significant changes in one's lifestyle may acutely lead to the development of psychological disorders, which with time patient may become adjusted to the situation.…”
Section: Discussionmentioning
confidence: 99%
“…9 One study conducted in Nepal found the prevalence of depression to be 51.8% which is lower than our study. 10 A study by Maharashtra, India, concluded that depression was the most common psychiatric comorbidity in patients undergoing haemodialysis (40.69%). 11 Another study conducted in the Middle East found the prevalence of depression and anxiety among patients undergoing haemodialysis to be 56.4% and 51.3% respectively.…”
Section: Discussionmentioning
confidence: 99%